Effectively Assessing Treatment Needs in Incarcerated Seriously Mentally Ill Individuals: The Utility of the Personality Assessment Inventory—Level of Care Index. (April 2018) - Leidenfrost, Corey M.; Scalco, Matthew D.; Randall, Elizabeth; Martin, Peter S.; Sinclair, Samuel J.; Stewart, Travis J.; Schoelerman, Ronald; Antonius, Daniel
Early identification of treatment needs in incarcerated individuals with serious mental illness has significant implications. Validated assessment instruments to guide treatment are lacking in correctional settings. Hierarchical linear modeling was used to examine the predictive validity of the Level of Care Index (LOCI) in 35 inmates admitted to a specialized treatment unit. The LOCI score was predictive of levels of depressogenic psychopathology and psychological well-being as well as changes in these constructs over time. These results validate the use of the LOCI in a correctional setting and demonstrate the utility of the LOCI to identify treatment trajectories.